Islamic Conservatism Negotiations: Women's Involvement In Saudi Arabian Football - Rachman, Auliyaur; Rodiah, Ita (Universitas Islam Negeri Sunan Kalijaga, 2024)
This research will discuss the dynamics of women's involvement in Saudi Arabian football and its influence on the culture of conservatism in that state. Saudi Arabia is known as a conservative state and tends to discriminate against women. However, in recent years, Saudi Arabia has begun to take an open and moderate stance, including in sports. This research is interesting to discuss because football, the most popular sport in Saudi Arabia, is a channel for creating a cultural transformation from conservative to moderate. This research aims to explain Saudi Arabia's efforts to change conservatism that has been rooted for a long time, through the involvement of women in football. This is descriptive qualitative research using library research methods and the approach refers to constructivism. The results of the research show that the role of Prince Muhammad bin Salman through Saudi Vision 2030 can change Saudi Arabia's culture of conservatism into a culture of moderation by relaxing existing norms such as allowing women to watch football matches in stadiums, establishing competitions and women's national team, being able to accommodate Saudi women to get involved in football and express their interests and talents after previously being restricted by the rules created by Wahhabism.